BEBERAPA PERMASALAHAN DAN UPAYA AKSELERASI PROGRAM PEMBERDAYAAN MASYARAKAT - W. Utomo, Tri Widodo (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Previously, government?s programs on people empowerment were considered to be failed in achieving their targets. One of the reasons is that the programs were improperly designed. At that time, policy on people empowerment was constantly associated to micro credit programs which in reality, unable to strengthen social and economic independency of the citizens. In such a case, this paper offers 5 categories of empowerment program that should be linked to 4 sectors of development, namely economic, social and cultural, political and administrative, and infrastructure dimension. Another important thing is that acceleration oof empowerment programs require political will of the government (booth in central and local level) to burst through and innovate every single public policy.